Sosialisasi Pemanfaatan Lahan Terbiarkan dengan Penanaman Tanaman Lokal Kalimantan Sebagai Upaya Konservasi Tanah dan Air: Sosialisasi Pemanfaatan Lahan Terbiarkan dengan Penanaman Tanaman Lokal Kalimantan - Karyati Karyati; Zulviana Devi; Sri Sarminah; Emi Purwanti; Nada Tasya Nuranda; Kusno Yuli Widiati; Karmini Karmini (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2022)
Local plants are plants that grow and develop in a certain area, and their distribution cannot be found in other areas. Currently the existence and popularity of local plants are starting to be replaced by the presence of several other types of plants from outside the region and even from abroad. The purpose of this community service was to socialize the use of abandoned land by planting local Kalimantan plants as an effort to save local Kalimantan plants that are threatened with sustainability and soil and water conservation. Community service is carried out in Bukit Biru Village, Tenggarong District, Kutai Kartanegara Regency, East Kalimantan Province where the majority of the people work as farmers. The method of service carried out is by conducting counseling, asking questions, and collecting feedback with the interview method using a questionnaire to the local community. The counseling on local plants that was carried out increased the community's understanding of the benefits and uses of local plants in daily life and other environmental benefits.